2017
DOI: 10.1093/jxb/erx294
|View full text |Cite
|
Sign up to set email alerts
|

Persulfidation proteome reveals the regulation of protein function by hydrogen sulfide in diverse biological processes in Arabidopsis

Abstract: Protein persulfidation in the Arabidopsis proteome is widespread and is the molecular mechanism by which hydrogen sulfide performs its signaling role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
282
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 259 publications
(289 citation statements)
references
References 81 publications
5
282
0
2
Order By: Relevance
“…In this sense, it should be point out the relevance of 6PGDH and NADP‐ME especially in situation with high content of NO and H 2 S, i.e. under stress conditions, because 6PGDH activity seems to be unaffected for these molecules whereas the NADP‐ME activity is only inhibited with higher concentration of both NO and H 2 S. Moreover, these data suggests that NADP‐ME could be modulated by S ‐nitrosation and persulfidation supporting previous reports in Arabidopsis, which indicate that this enzyme could be a target of these posttranslational modifications (Chaki et al , Aroca et al ).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In this sense, it should be point out the relevance of 6PGDH and NADP‐ME especially in situation with high content of NO and H 2 S, i.e. under stress conditions, because 6PGDH activity seems to be unaffected for these molecules whereas the NADP‐ME activity is only inhibited with higher concentration of both NO and H 2 S. Moreover, these data suggests that NADP‐ME could be modulated by S ‐nitrosation and persulfidation supporting previous reports in Arabidopsis, which indicate that this enzyme could be a target of these posttranslational modifications (Chaki et al , Aroca et al ).…”
Section: Resultssupporting
confidence: 89%
“…As in this study of NADP‐ME, using in vitro assays, we previously found that NADP‐ICDH activity in pepper fruits is inhibited in the presence of H 2 S donors. In both cases, the in vitro data are closely in line with the findings of proteomic analysis carried out in Arabidopsis (Aroca et al ). However, it is important to point out that no NADP‐dehydrogenase in the oxidative pentose phosphate pathway (OxPPP) was affected by H 2 S, indicating that the data obtained are reliable and contain no artifacts.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The majority of studies identifying and examining the biochemical functions of sulfhydration are primarily constructed on cell culture models and/or with purified proteins in vitro. One of the few studies to examine the total number and identity of sulfhydrated proteins, or sulfhydrome, of an organism in vivo was completed in the plant Arabidopsis thaliana, with the discovery of 2,015 proteins, or approximately 5% of the entire proteome, as sulfhydrated (Aroca et al, 2017). However, the sulfhydrome profiles and their associated biological functions of major organs in a mammal, particularly under dietary and/or genetic conditions known to impact endogenous H2S production, have not been described.…”
Section: Introductionmentioning
confidence: 99%
“…Such modification usually increases the catalytic activity of the target proteins because it merely changes an -SH to an -SSH, enhancing the enzymes' chemical reactivity and possibly improving access to their respective targets [133]. However, the significance of S-sulfhydration in autophagy has not been sufficiently explored and proteomic analysis performed on wild type plants revealed the susceptibility of only four autophagy-related proteins, ATG18a, ATG3, ATG5, and ATG7, to persulfidation [134]. Incidentally, the role of H 2 S in modulating iron availability in maize seedlings grown in iron-deficient conditions was recently reported [135].…”
Section: Selective Degradation Via Autophagy In the Regulation Of Sulmentioning
confidence: 99%